A rare case report of amniotic band syndrome associated with gastroschisis and limb body wall complex - Rita D.; Pushpalatha V. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The amniotic band syndrome can cause a wide range of anomalies and the most common associated anomalies include amputations, constriction bands, encephalocele, acrania, syndactyly, craniofacial defects, club feet and cleft lip. Vertebral and abdominal wall defects such as gastroschisis and scoliosis are extremely rare. A 19-year-old female, G1P0 (primi) presented to our outpatient department for her first antenatal visit at 14 weeks + 6 days’ period of gestation according to her LMP. Ultrasonography (USG) features suggestive of limb body wall complex/ amniotic band syndrome, undergone MTP after counselling. In amniotic band syndrome there is no known inheritance pattern. The prognosis in case of amniotic band syndrome is dependent on the specific anomalies present. Severe and complex malformations as seen in this case are incompatible with extra uterine life and are an indication for termination of pregnancy. This condition is diagnosable prenatally. It can also lead to lethal deformation of vital internal organs in rare cases. Because limb body wall complex is incompatible with life, early diagnosis is crucial for parental counseling.